EFEKTIVITAS SISTEM PENGARSIPAN BERBASIS TEKNOLOGI DI SEKRETARIAT DPRD PROVINSI RIAU - Syahruddin; Rijalul Fikri (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
Digital transformation in governance has driven the adoption of technology-based archiving systems in various public institutions. This study aims to analyze the effectiveness of digital archiving system implementation, focusing on the PERISAI (Portal Elektronik Register Informasi Jabatan Fungsional Satu Instansi) Application at the Regional People's Representative Council (DPRD) Secretariat of Riau Province. Using a qualitative literature study method, this research examines recent literature on e-government implementation, particularly in the context of legislative archives management. The results show that PERISAI implementation has achieved a 90% adoption rate, with a 35% increase in time efficiency for document retrieval and up to 60% reduction in paper usage. Critical factors influencing implementation success include leadership commitment, infrastructure readiness, and staff competency development. However, challenges such as the digital divide between generations and integration with other information systems still need to be addressed. This study concludes that PERISAI has significant potential in improving efficiency and transparency in local government governance, although its implementation requires a holistic approach considering technological, organizational, and human aspects. These findings provide important implications for e-government policy development and digital archive management practices in Indonesia's public sector.